The Relationship Between "What We Believe" and "How We Care" Among Daughters Caring for a Parent With Dementia. (March 2017) - Chen, Cory K.; Clayton, Karima; Chodosh, Joshua
This study attempted to better understand factors associated with relationship conflict between daughters and their parents with dementia. We examined data from 77 daughters self-identified as primary caregivers of a parent with dementia to test the hypothesis that daughters' belief that a parent with dementia can control their symptoms is associated with more conflict, defined as high expressed emotion (EE). Participants completed self-report questionnaires assessing beliefs about parents' ability to control symptoms, stress, relationship conflict, parent agitation, and cognitive status. Results indicated that greater intensity of daughters' belief that their parent can control dementia-related symptoms was associated with more relationship conflict or "high EE" (β = 0.57, P < .001). Daughters' beliefs about parental behavior may contribute to caregiver stress and exacerbate negative behaviors exhibited by individuals with dementia. Educating caregivers about parental behaviors and examining factors underlying caregiver interpretations of these behaviors hold promise for reducing caregiver stress.